2012
DOI: 10.5455/msm.2012.24.84-86
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic and Lipid and #8211;lowering Effects of Statins in Hypertension

Abstract: Background:Data on the lowering effects of statins in hypertensive patients have been mixed and highly controversial. Some studies shows reductions effects of statins in blood pressure, whereas others do not. The evidence in the literature on the effects of statins on blood pressure raises the possibility that statins may directly lower blood pressure in addition to reduce cholesterol levels–pleiotropic effects of statins.Aim of the study:The role of statins as additional treatment in patients with severe hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…All parameters of elasticity (strain and distensibility) were compromised in aorta of the severe long-standing hypertension group compared to control group. These parameters were not related to age as in many trials has been proved (24, 25, 26) since control group and SLH group were with no age difference statistically; we consider that these changes are due to atherosclerosis as it is reported in many studies that atherosclerosis reduce elasticity of big arteries (27, 28, 29), atherosclerosis have been often found in our hypertensive patients (30). These data are in concordance with data of reported from Vitarelli A. et.…”
Section: Discussionmentioning
confidence: 58%
“…All parameters of elasticity (strain and distensibility) were compromised in aorta of the severe long-standing hypertension group compared to control group. These parameters were not related to age as in many trials has been proved (24, 25, 26) since control group and SLH group were with no age difference statistically; we consider that these changes are due to atherosclerosis as it is reported in many studies that atherosclerosis reduce elasticity of big arteries (27, 28, 29), atherosclerosis have been often found in our hypertensive patients (30). These data are in concordance with data of reported from Vitarelli A. et.…”
Section: Discussionmentioning
confidence: 58%
“…Evidence from some other studies shows that statins have positive effects on atherosclerotic regression and enhance the effect of FDC on arteries. 52 55 In the ASCOT trial, significant differences in the rates of myocardial infarction and stroke were observed between patients on atorvastatin and amlodipine (+ perindopril) and those on amlodipine (+ perindopril) only. 55 The authors explained it by the synergetic action of amlodipine (restoring of vascular tonus, improvement of endothelial function, decrease in smooth myocyte migration, etc), perindopril (endothelial oxidative stress reduction, improvement of endothelial function, reduction of thrombocyte aggregation, vasodilation, reduction of atherosclerotic biomarkers [D-dimer, cytokines, TNF-α], and apoptosis), and atorvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrier et al [20] additionally showed that the use of statin in patients with isolated systolic hypertension significantly improved systemic arterial compliance (0.43 ± 0.05 vs. 0.36 ± 0.03 mL/mm Hg, p = 0.03) measured noninva- All-cause mortality and cardiovascular mortality outcomes by subgroup sively by carotid applanation tonometry and Doppler velocimetry of the ascending aorta. This synergistic effect stemming from the combination of antihypertensive therapy and statins appears to transcend cholesterol reduction uniquely and suggests a more intricate form of statin-mediated vascular pleiotropic effect [21,22]. As previously mentioned, lipid-lowering therapy is an important cornerstone in the management of all patients with CKD not on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ge et al [19] showed that the combination of statin and antihypertensive therapy compared to antihypertensive therapy alone allowed better SBP control (123 ± 12 vs. 137 ± 11 mm Hg, p < 0.05), lower high-sensitive C-reactive protein levels, and improved cardiac remodeling (left ventricular mass index: 103 ± 32 vs. 111 ± 38 g/m 2 , p < 0.05) [19]. Kamberi et al [21] described that atherosclerotic plaque regression resulting from statin use led to better responses to BP-lowering therapy in hypertensive patients. Ferrier et al [20] additionally showed that the use of statin in patients with isolated systolic hypertension significantly improved systemic arterial compliance (0.43 ± 0.05 vs. 0.36 ± 0.03 mL/mm Hg, p = 0.03) measured noninva- All-cause mortality and cardiovascular mortality outcomes by subgroup sively by carotid applanation tonometry and Doppler velocimetry of the ascending aorta.…”
Section: Discussionmentioning
confidence: 99%